Community Capacity Building in Sexually Transmitted Disease Prevention in Hongkong - Cahyati, Widya Hary; Rahayuningsih, Margareta; Savitri, Annisa Aulia; Meviana, Dliya Laela Eka; Muhammad, Fathurrahman; Anakita, Cantika Salya Manikawening (Universitas Negeri Semarang, 2025)
Sexually transmitted diseases (STDs) represent a persistent and evolving public health challenge globally. In Hongkong, various community-based organizations have been instrumental in reaching underserved populations with culturally competent sexual health services. However, despite the growing importance of community actors, they often operate with limited resources, face inconsistent support from public institutions, and struggle with sustainability. Many community organizations lack sufficient training, funding, data access, and policy influence to operate at full capacity and to scale their work meaningfully. The community service activities carried out in this initiative have shown significant positive outcomes in enhancing the knowledge and attitudes of Indonesian female migrant workers in Hongkong regarding reproductive health and STD prevention. Through culturally sensitive counseling and the distribution of educational leaflets in Bahasa Indonesia, the program successfully reached a population that often faces barriers to health information and services. Participants demonstrated a clear increase in understanding of basic reproductive health topics, including STD symptoms, transmission methods, and preventive behaviors. More importantly, the activities helped normalize conversations around sexual health, reducing stigma and empowering women to seek testing and medical support when necessary. The peer-led approach played a crucial role in building trust and encouraging open dialogue. In conclusion, this initiative demonstrates that targeted, culturally relevant community service activities can effectively improve both awareness and attitudes toward reproductive health among marginalized groups. Strengthening such community-based efforts will be essential for advancing sexual health equity and preventing STDs among migrant populations in Hongkong and beyond.